Rebooting the World Trade Organization: A Rethink on Purpose and Practice - Amrita Narlikar (CESifo Forum, 2021)
The World Trade Organization (WTO) has gone through stormy times. There have been a number of serious controversies in recent years. Many of these have been attributed to the disruptive positions that former US President Donald J. Trump has taken on international trade and multilateral institutions. But that is just one of numerous, deep and long-standing problems plaguing the WTO. Most notably, it is struggling with the fact that its "trade liberalization" function has become a blunt sword. Discussions about reforming the WTO have been triggered by increasing competitive tensions among the United States, the EU and China. At the same time, China has become an increasingly powerful force within the global trading system. This edition of the CESifo Forum examines the current challenges facing international trade and global cooperation systems. The authors discuss the future of the WTO and proposals to reform it that will make trade multilateralism meaningful again.
Keywords: 330